Islamic Ethics in Medical Device Business During The Covid-19 Pandemic - Nurandani, Annisa; Ibrahim, Muhammad Yusuf; Lubis, Rusdi Hamka (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2022)
This study aims to examine ethical values from the point of view of Islamic religious teachings in the medical device business during the COVID-19 pandemic. In this case, three major discussions were carried out, namely reviewing Islamic ethical standards in business in a special situation, describing medical device business practices that are not by Islamic ethics in reality, and Islamic criticism of these practices. The results of the study explain that there are violations that are not by Islamic business ethics in the medical device business during this pandemic. And there is a proposed solution to overcome this, namely, the related producers better collaborate with the government so that distribution in the market is more secure. And the government is also expected to maintain confidence in managing the needs of the community in a crisis like this. As is done in the United States by giving production rights to private entrepreneurs, distribution is determined by the government to maintain prices and distribute evenly to the community.